A practical approach to non-spectral interferences elimination in inductively coupled plasma optical emission spectrometry - Krejčová, Anna; Černohorský, Tomáš; Bendakovská, Lenka (Springer, 2016)
Matrix effects and practical possibilities of reducing accompanying non-spectral interferences in inductively coupled plasma optical emission spectrometry (ICP-OES) were studied for microconcentric Micromist, concentric and V-groove nebulizers (VGN) coupled with two cyclonic spray chambers of different sizes. The effect of a wide scale of interferents and mixtures thereof in the concentration range of up to 2 mass % (Na, Ca, Ba, La, urea) or up to 20 vol. % (nitric acid) on the analysis of Cd, Cu, K, Mg, Mn, Pb and Zn was investigated in terms of their analytical recovery and Mg(II) 280.27 nm/Mg(I) 285.29 nm line intensity ratio. Recoveries of ionic lines were lower than those of atomic lines (37-102 %) depending on the matrix concentration. The Mg(II)/Mg(I) ratios were found to be 12-15 and they slightly decreased as the matrix load increased. Exceptional behavior of pure La matrix, steeply lowering the recoveries and Mg(II)/Mg(I) ratios was observed. A Micromist nebulizer coupled with a small inner volume spray chamber provided the highest recoveries (94-102 %), lowest matrix effects across the matrix loads and, compared to others, the least significant dependence without worsening of the analytical characteristics (recoveries, signal background ratios and the Mg(II)/Mg(I) ratios) across the studied matrices. (C) 2016 Institute of Chemistry, Slovak Academy of Sciences
Praktický příspěvek k eliminaci nespektrálních interferencí v ICP OES
Keywords: ICP-OES; matrix effect; microconcentric Micromist nebulizer; spray chamber